1992
DOI: 10.1007/bf02221676
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is not involved in the initiation of insulin secretion from rat islets of Langerhans

Abstract: The involvement of nitric oxide as an intracellular messenger in the control of insulin secretion from pancreatic Beta cells was studied in rat islets of Langerhans by measuring: (i) nitric oxide generation in response to physiological insulin secretagogues; (ii) the effects of inhibitors of nitric oxide synthesis on insulin secretory responses to physiological secretagogues, and on insulin synthesis; (iii) changes in islet cyclic guanosine monophosphate in response to secretagogues; (iv) the effects of exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 30 publications
8
48
0
1
Order By: Relevance
“…the fi cell physiological stimulus, with respect to the conflicting reports as to the ability of glucose to induce NO formation (Jones et al, 1992;Schmidt et al, 1992) our data agree with an activation of the constitutive form of NO synthase by glucose. However, unlike the stimulating effect on insulin secretion previously proposed, our results bring evidence for an inhibitory effect; addition of L-NAME at increasing concentrations, when performed prior to and during high glucose, progressively converted the biphasic pattern of fi cell response into a greater monophasic one, whereas D-NAME was without effect.…”
Section: Discussionsupporting
confidence: 83%
“…the fi cell physiological stimulus, with respect to the conflicting reports as to the ability of glucose to induce NO formation (Jones et al, 1992;Schmidt et al, 1992) our data agree with an activation of the constitutive form of NO synthase by glucose. However, unlike the stimulating effect on insulin secretion previously proposed, our results bring evidence for an inhibitory effect; addition of L-NAME at increasing concentrations, when performed prior to and during high glucose, progressively converted the biphasic pattern of fi cell response into a greater monophasic one, whereas D-NAME was without effect.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the present study are in agreement with in vitro and in vivo studies in animals showing that although NO is a mediator of glucose-induced cGMP production in islets, the resulting increase in cGMP is not correlated with insulin secretion (31). Moreover, Pueyo et al (19) have shown that the administration of N-nitro-L-arginine methyl ester in vivo markedly diminished NO-dependent cGMP production without affecting insulin secretion .…”
Section: Euglycemic-hyperinsulinemic Clampsupporting
confidence: 91%
“…Although increases in cyclic GMP have been linked with decreases in insulin secretion [44,45], the role of this nucleotide in the islet beta cell remains unclear [46,47]. More recent studies suggest that cyclic GMP could mediate the effects of low concentrations of nitric oxide in augmenting glucose-induced Ca 2+ oscillations and insulin secretion in rat-isolated beta cells [48,49,50].…”
Section: Cyclic Gmpmentioning
confidence: 99%